STUDI ARUS INVESTASI LANGSUNG DAN TIDAK LANGSUNG DI ASEAN 4 DALAM PERSPEKTIF MARGIN INTENSIF DAN EKSTENSIF - Yuniasih, Diah Retno; Santosa, Siswoyo Hari; Luthfi, Agus (EP FEB UNS, 2018)
Globalization in economic has an impact on the massive movement of foreign direct (FDI) and indirect (Foriegn Private Investment / FPI) investments in developing countries in the world. By intensive margin government and authority in each country utilizes these conditions as development capital and technology transfer, while for extensive margin foreign investment are used to maintain a conducive relationship between investors and investment destination countries. Foreign investment is an important part of development especially for developing countries. For ASEAN 4 countries investment is very useful as a driver of the national economy, so the consideration of a stable investment climate and macroeconomic environment is important in policy formulation. The method used to analyze the relationship to the intensive and extensive margins of FDI and FPI in ASEAN 4 is the Panel Least Square (PLS) with annual panel data from Indonesia, Malaysia, Philippines and Thailand from 2003 to 2015. The estimation results show that on extensive margins GDP show a positive and significant effect on FDI. While on the FPI model estimation, the three proxy variables (Index Perception Corruption (IPK), Inflation Rate (TI), and lending rate) used indicate a positive direction towards FPI on intensive and extensive margins, but only IPK variable that have positive and significant influence. This is indicated by probalitity value less than 5% (0.05) that is equal to (0.005).Keywords : Extensive Margin, Foreign Direct Investment, Foreign Private Investment, Intensive Margin, Panel Least Square.